Efficacy and Economics of Different Soil Sampling Grid Sizes for Site-Specific Nutrient Management in Southeastern USA - Simerjeet Virk; Matthew Tucker; Glendon Harris; Amanda Smith; Matthew Levi; Jason Lessl (Agronomy)
Precision soil sampling on larger grid sizes (≥2.0 ha) is a common practice to reduce the number of soil samples and associated sampling costs. A study was conducted to evaluate the influence of different grid sizes on the depiction of spatial nutrient variability and their influence on the accuracy of variable-rate fertilizer application and total application costs. Soil sampling was conducted in nine agricultural fields using grid sizes of 0.4, 1.0, 2.0, 3.0, and 4.0 ha, and the resulting variable-rate prescription maps for lime, P, and K were spatially analyzed and compared with a reference map (generated from high-density soil sampling; approximately 2.5 samples per hectare) to determine the amount of under-, on-target, and over-application that would occur within each field. An economic analysis was conducted including the soil sampling costs, soil analysis costs, and nutrient costs to determine the effect of grid size on total application costs. Soil sampling on a 0.4 ha grid size had the best performance in depicting the spatial variability of soil pH, P, and K within the fields, and exhibited the highest application accuracy for the variable-rate prescription maps. The general trend was that the application accuracy decreased with an increase in grid size, with the potential for the under- and over-application of nutrients significantly increasing at the larger grid sizes of ≥2.0 ha. The total application cost varied among the fields as it was largely influenced by the amount of under- and over-application associated with each grid size. In most fields, the total application costs for a 0.4 ha grid size were lower or comparable to other grid sizes. In some fields, the larger grid sizes exhibited lower application costs but at the expense of reduced application accuracy. Overall, the results suggest that the smaller grid sizes of ≤1.0 ha are optimal for soil sampling in agricultural fields to ensure accurate and cost-effective variable-rate applications for site-specific nutrient management.